STRATEGIES FOR NITRATE REDUCTION IN A CONTAMINATED COASTAL AQUIFER BY AGRICULTURAL PRACTICES CAPARICA, PORTUGAL - Martinez, Jorge Luis; Mancuso, Malva; Ribeiro, Manuela Simões (Águas Subterrâneas, 2011)
This research compared the applicability of remediation technologies to reduce nitrates in groundwater in a coastal aquifer at Terras da Costa de Caparica, Portugal. The purpose of the study was to select a pilot area in Terras da Costa in order to assess the applicability of the following in situ remediation technologies: Fitoremediation, Permeable Reactive Barrier and Enhanced In Situ Biodenitrification. Advantages and disadvantages of each technology were discussed and presented in a comparison matrix for decision and proposal of future pilot tests. It was concluded that no technical or practical factors would impede the application of the above technologies in the pilot area.